Mechanistic Insight Into the Antifungal Effects of a Fatty Acid Derivative Against Drug-Resistant Fungal Infections - Bhattacharyya, Anamika; Sinha, Mau; Singh, Himanshi; Patel, Ranjeet Singh; Ghosh, Sumana; Sardana, Kabir; Ghosh, Shamik; Sengupta, Shiladitya (Frontiers in Microbiology, 2020)
Drug-resistant pathogenic fungi are emerging as a major global health challenge. There is an urgent need for novel molecules that can exert a potent antifungal activity and overcome resistance. Elucidating novel anti-fungal properties of existing molecules can potentially offer a rapid solution to address this emerging threat. We rationalized that molecules which disrupt the fungal cell membrane could address the above unmet need. As fatty acids underpin the formation and stability of cell membranes, we used computational simulations to evaluate the interactions between selected short chain fatty acids and a model cell membrane. Here, we report that caprylic acid could penetrate and perturb the membrane in silico. Based on the in silico findings, we identified a derivative of this fatty acid that disrupts fungal membranes as detected using steady-state fluorescence anisotropy. We show that this fatty acid derivative is potent against a variety of fungal pathogens like Candida and Trichophyton. We further demonstrated the ability of this fatty acid derivative to potentiate some azoles in vitro and enhance the efficacy of antifungal formulations in vivo. Our data suggests the emergence of a novel therapy for effective disease management and overcoming anti-fungal drug resistance.